Innovation and education: unlimited potential for the teaching library. - Moore, M (1989)
The information age demands that health sciences librarians take active roles in the educational process. Librarians have traditionally taught users how to access information. Now, with the proliferation of information, librarians must accept new roles and teach the user efficient techniques for evaluating and processing information as well. Innovative roles for librarians at Texas Tech University Health Sciences Center include teaching users to use technology for information management, to appraise literature critically for quality, and to develop skills for lifelong learning. This paper reviews the history of educational activities in health sciences libraries and describes the teaching programs at Texas Tech.